Assessment of the Noxious Effects of Lithium Carbonate on Granular Cell Layer of Rat Cerebellum (Medical Forum Monthly, 2021)
Objective: To evaluate and document the effects of ingestion of i.e. of 34 mg/kg body weight/OD of lithium carbonate on Cerebellar Granular cell layer.Study Design: Prospective Experimental researchPlace and Duration of Study: This study was conducted at the Basic medical sciences institute Jinnah post graduate medical Centre Karachi, from June, 2012 till August, 2012.Materials and Methods: This present study is designed to observe the microscopic changes of Granular cell layer in rat cerebellum. For this experimental study 20 animals weighing 170-175 grams were selected, they were divided into two groups, each comprising of 10 animals. Control group-A were given lab diet and water for a time period of 12 weeks while the rats in group-B received Lithium Carbonate dissolved in distill water given orally by tube 34 mg/kg body7 weight/OD for 12 weeks respectively.Results: Our study documented decreased granular cell layer thickness in group B animals, after they had ingested Lithium carbonate for 12 weeks as compared to the Group A animals on lab diet.Conclusion: The changes of the thickness of cerebellar Granular cell layer was found to be highly significantly decreased in group B animals treated with Lithium than group A rodents which were placed only on lab diet. Lithium carbonate caused apoptosis and injury to Cerebellar Granular layer.